Testing the bond strength between acrylic teeth and denture base - Clin Prof Robert Ćelić; Dr Martin Pavlin; Prof Nenad Gubeljak; Assist Prof Nikola Petričević; Dr Hrvoje Pezo (Elsevier, 2023)
Aim or Purpose: The aim of this study was to investigate the quality of the bond between the acrylic tooth and the denture base after compressive loading of acrylic complete dentures regarding the reinforcement of the denture base and different types of treatment of the surfaces of the acrylic teeth. Materials and Methods: The sample consisted of 4 pairs of acrylic complete dentures, two pairs of which had denture base reinforcement (carbon fibres) and two pairs without base reinforcement. The surfaces of the acrylic teeth that came into contact with the acrylic dough during the flasking process were treated in four ways (no treatment, roughening, monomer coating and mechanical-chemical treatment). A one-factor analysis of variance was used to investigate the influence of the reinforcement of the base of complete dentures and the different types of treatment of the surface of the acrylic tooth on the quality of the bond (statistical significance level of p ˂ 0.01). Results: The result of the one-factor analysis of variance (Welch's F-test) shows that there is a statistically significant difference between the arithmetic means of the measured gap sizes (ranged between 40 and 120 microns) in relation to the different types of treatment of the surface of the acrylic tooth. Conclusions: The microscopic analysis showed that the size of the gap at the interface between the acrylic tooth and the base of the complete dentures was influenced by the mechanical-chemical treatment method of the surface of the acrylic tooth, while the reinforcement of the base with carbon fibres had no effect on the quality of the bond.